Effect of oxidant quantity and humidification temperature on performance of PEMFC with twin inlet and twin outlet flow field - Jose, Aneesh; Bekal, Sudesh; Revankar, Shripad T. (Frontiers in Energy Research, 2024)
The paper presents an analysis of the performance of a Proton Exchange Membrane (PEM) fuel cell, which is equipped with a flow field design featuring dual inlets and outlets, while operating under conditions of excess stoichiometry. These experiments were conducted using a fuel cell system connected to a station that allowed for the precise adjustment of gas flow rates. During the initial phase of experimentation, various proportions of excess oxygen were systematically applied, while maintaining constant hydrogen flow rates of 80 mL/min and 100 mL/min. Particularly noteworthy, for the case of a 100 mL/min hydrogen gas flow rate and the optimized excess oxygen proportion of 150%, further experiments were undertaken to ascertain the ideal humidification conditions. The outcomes of these experiments revealed that a hydrogen gas flow rate of 100 mL/min consistently outperformed the 80 mL/min flow rate in terms of fuel cell performance. Moreover, it was observed that the introduction of excess oxygen significantly improved performance, up to a 50% oxygen proportion for the 80 mL/min hydrogen flow rate and up to a 150% proportion for the 100 mL/min hydrogen flow rate. One intriguing observation pertained to the influence of humidification. Specifically, it was found that the utilization of a humidification temperature of 100°C, or the absence of humidification altogether, resulted in notably diminished power output. In contrast, intermediate humidification temperatures of 60°C, 70°C, 80°C, and 90°C consistently yielded identical maximum power points (MPP) when combined with a 150% excess oxygen supply and a hydrogen flow rate of 100 mL/min. The twin inlet-twin outlet flow field provides a slight advantage over the conventional serpentine flow field in the overall analysis.